2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591254
|View full text |Cite
|
Sign up to set email alerts
|

Dental plaque assessment lifelogging system using commercial camera for oral healthcare

Abstract: We present a system for estimating the dental plaque adhesion area using a commercial camera image for oral healthcare via management of the intraoral environment. In recent years, several studies have reported on the relationship between a general disease and a periodontal disease. Such studies mention that normalization of the intraoral environment by tooth brushing is the most important treatment in preventive dentistry. However, evaluation of individual tooth brushing skill is difficult. Some devices for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…The results obtained from both techniques correlate to the orthopaedic radiologists' diagnosis. Kasai et al (2016) present a system for estimating the dental plaque adhesion area using a commercial camera image for oral healthcare via management of the intraoral environment. They suggested an estimation procedure for the volume of dental plaque applied for Plaque Control Record (PCR) replacement.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from both techniques correlate to the orthopaedic radiologists' diagnosis. Kasai et al (2016) present a system for estimating the dental plaque adhesion area using a commercial camera image for oral healthcare via management of the intraoral environment. They suggested an estimation procedure for the volume of dental plaque applied for Plaque Control Record (PCR) replacement.…”
Section: Introductionmentioning
confidence: 99%
“…The color threshold was performed using the Otsu method, since: 1) it was the method of Kasai et al . ( 15 ), for image processing; 2) it transforms the image into binary, and 3) allow automatic image thresholding ( 16 ). Preliminary statistical analysis indicated that HSB coding was more successful in discriminating the sample classes than RGB coding.…”
Section: Methodsmentioning
confidence: 99%
“…The tool used is compatible with all types of cameras. However, it is still difficult to maintain individual dental health (9) . Children need a tool to play in order to develop their abilities (10) .…”
Section: Introductionmentioning
confidence: 99%